All-solid-state battery and electric equipment
By using electrode materials with the same type of crystal structure as solid electrolyte in all-solid-state lithium batteries or setting up metal lithium negative electrodes, the problem of high interface impedance is solved, and rapid lithium ions transportation and battery performance are achieved.
Patent Information
- Application Number
- CN202510118866.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-05-02
AI Technical Summary
Due to the solid-solid contact between the positive and negative electrodes and the electrolyte, all-solid lithium batteries are prone to generate large interface impedance, hindering the rapid transport of lithium ions and affecting battery performance.
The positive electrode active material and negative electrode active material with the same crystal structure type as the solid electrolyte, or the negative electrode sheet is set as metal lithium to enhance the lattice matching at the interface and reduce the interface impedance.
By improving the lattice matching at the interface and reducing the interface impedance, lithium ions can pass through the interface quickly, improving the performance of all-solid-state batteries.
Smart Images

Figure CN119920997A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of batteries, and more specifically, to an all-solid-state battery and electrical equipment. Background Art
[0002] As the demand for high-safety, high-energy-density lithium-ion batteries continues to grow, solid-state lithium batteries that use solid electrolytes to replace traditional liquid electrolytes have attracted much attention in recent years.
[0003] Solid-state lithium batteries work on the same principle as liquid lithium batteries. The movement of lithium ions from the positive electrode to the negative electrode and then back to the positive electrode represents the battery's charge and discharge process. However, in solid-state batteries, the transport medium for lithium ions between the positive and negative electrodes is replaced by an inorganic solid electrolyte from an organic liquid electrolyte, thereby improving the safety of the battery. However, the contact mode between the positive and negative electrodes and the electrolyte is also changed from solid-liquid contact to solid-solid contact, which easily produces a large interface impedance, hindering the rapid transport of lithium ions, thereby affecting battery performance. Summary of the invention
[0004] In view of the above problems, the present application proposes an all-solid-state battery and electrical equipment, which can increase the lattice matching at the interface, reduce the interface impedance, allow lithium ions to pass through the interface quickly, and improve the performance of the all-solid-state battery.
[0005] In a first aspect, an embodiment of the present application provides an all-solid-state battery, comprising a positive electrode sheet and a negative electrode sheet, and a solid electrolyte layer arranged between the positive electrode sheet and the negative electrode sheet, the solid electrolyte layer comprising a crystalline solid electrolyte, the solid electrolyte comprising at least one of a perovskite solid electrolyte, an anti-perovskite solid electrolyte and a LISICON solid electrolyte, the positive electrode sheet comprising a positive electrode active material; wherein the negative electrode sheet comprises a negative electrode active material, and at least one of the positive electrode active material and the negative electrode active material is of the same type as the crystal structure of the solid electrolyte; or, the negative electrode sheet is metallic lithium, and the positive electrode active material is of the same type as the crystal structure of the solid electrolyte.
[0006] In the technical solution of the embodiment of the present application, on the basis that the solid electrolyte includes at least one of a perovskite solid electrolyte, an antiperovskite solid electrolyte and a LISICON solid electrolyte, the negative electrode sheet includes a negative electrode active material, and the positive electrode active material and at least one of the negative electrode active materials have the same type of crystal structure as the solid electrolyte; or, the negative electrode sheet is metallic lithium, and the positive electrode active material has the same type of crystal structure as the solid electrolyte. This arrangement can increase the lattice matching at the interface, reduce the interface impedance, allow lithium ions to pass through the interface quickly, and improve the performance of the all-solid-state battery.
[0007] In some embodiments, the positive electrode active material, the negative electrode active material, and the solid electrolyte have the same type of crystal structure.
[0008] In some embodiments, the solid electrolyte is an antiperovskite solid electrolyte; the positive electrode active material is an antiperovskite positive electrode active material; and / or the negative electrode active material is an antiperovskite negative electrode active material.
[0009] In some embodiments, the solid electrolyte comprises at least one of Li7O2X3, Li3OX, and Li2OHX, wherein X comprises F - , Cl - Br - ,I - 、NO 2- NH 2- , BH 4- and BF 4- At least one of .
[0010] Optionally, the positive electrode active material includes Li x TM y ChD b , and / or, the negative electrode active material includes amorphous Li x TM y ChD b ; Where TM is a transition metal, Ch is a chalcogen element, and D is O or B a C 1-a , B is selected from at least one of negative monovalent anions and negative monovalent anion clusters, C is selected from at least one of negative trivalent anions and negative trivalent anion clusters, 0.5≤x≤8, 0.8≤y≤1.1, 0.25≤a≤0.75, 0.8≤b≤1.2.
[0011] Optionally, TM includes at least one of Fe, Co, Mn, Ni, Cu, Cr, V, Ti, W, Si, Sn and Nb; Ch includes at least one of S, Se and Te; B includes F - , Cl - Br - ,I - , H - OH - 、BH4 - NH2 - 、NO2 - and CN - At least one of; C includes N 3- 、(PO4) 3- 、(SbO4) 3- and (AsO4) 3- At least one of .
[0012] In some embodiments, the solid electrolyte is a LISICON solid electrolyte; the positive electrode active material is a positive electrode active material having a LISICON crystal structure; and / or the negative electrode active material is a negative electrode active material having a LISICON crystal structure.
[0013] In some embodiments, the solid electrolyte includes Li 14 ZnGe4O 16 , Li 3+x Cr 1-x Ge x O4, Li 3.6 Ge 0.6 V 0.4 O4, Li 4-2x Co x GeO4, Li 3.25 Si 0.25 P 0.75 O4, Li 3.53 (Ge 0.75 P 0.25 ) 0.7 V 0.3 O4, Li4Al 1 / 3 Si 1 / 6 Ge 1 / 6 P 1 / 3 O4, and Li 3.5 Ge 0.5 V 0.5 At least one of O4, where 0≤x≤0.5.
[0014] Optionally, the positive electrode active material includes Li3V2(PO4)3; and / or, the negative electrode active material includes LiV2(PO4)3.
[0015] In a second aspect, the present application provides an electrical device, which includes the all-solid-state battery in the above embodiment, and the all-solid-state battery is used to provide electrical energy to the electrical device.
[0016] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:
[0018] Figure 1 The charge and discharge curves of the antiperovskite cathode / antiperovskite electrolyte / metal lithium all-solid-state battery and the AC impedance spectra of some components provided in Example 1;
[0019] Figure 2 A schematic diagram of the structure of an antiperovskite positive electrode / antiperovskite electrolyte / antiperovskite negative electrode all-solid-state battery provided in Example 2;
[0020] Figure 3 The charge and discharge curves and AC impedance spectrum of the anti-perovskite cathode / anti-perovskite electrolyte / metal lithium all-solid-state battery provided in Comparative Example 1;
[0021] Figure 4 The charge and discharge curves and AC impedance spectrum of the half-cell of Si negative electrode / solid electrolyte Li2OHCl / lithium metal provided in Comparative Example 2. DETAILED DESCRIPTION
[0022] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0023] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0024] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0025] In the description of the embodiments of the present application, the term "and / or" is merely a term used to describe the association relationship between associated objects, indicating that three relationships may exist. For example, A and / or B may represent three situations: A exists alone, A and B exist at the same time, and B exists alone.
[0026] Since the contact mode between the positive and negative electrodes and the electrolyte of all-solid-state batteries has also changed from solid-liquid contact to solid-solid contact, it is easy to produce a large interfacial impedance, which hinders the rapid transport of lithium ions and thus affects the battery performance. Therefore, based on the existing high-ionic conductivity solid electrolytes, constructing an electrode-solid electrolyte interface for rapid lithium ion transport is one of the important technical difficulties in the current development of solid-state lithium batteries.
[0027] At present, the main methods to reduce interfacial impedance are: densifying the interface through high-temperature heat treatment, increasing the contact area and thus reducing the interfacial impedance, but the effect is not good for the lattice-mismatched electrode and electrolyte interfaces; by adding an organic polymer modification layer between the electrode and the electrolyte, the interface wettability is increased, thereby reducing the interfacial impedance, but the introduction of an additional buffer layer will increase the battery manufacturing cost.
[0028] The present application uses electrode materials and solid electrolyte materials with similar crystal structure types to assemble a full battery on the basis of a solid electrolyte including at least one of a perovskite solid electrolyte, an antiperovskite solid electrolyte and a LISICON solid electrolyte. This not only takes into account good electrochemical performance, but also increases the lattice matching at the interface, reduces the interface impedance, and allows lithium ions to pass through the interface quickly.
[0029] The present application provides an all-solid-state battery, which includes a positive electrode sheet and a negative electrode sheet, and a solid electrolyte layer arranged between the positive electrode sheet and the negative electrode sheet, the solid electrolyte layer includes a crystalline solid electrolyte, the solid electrolyte includes at least one of a perovskite solid electrolyte, an anti-perovskite solid electrolyte and a LISICON solid electrolyte, and the positive electrode sheet includes a positive electrode active material.
[0030] Wherein, the negative electrode sheet includes a negative electrode active material, and at least one of the positive electrode active material and the negative electrode active material has the same type of crystal structure as the solid electrolyte; or, the negative electrode sheet is metallic lithium, and the positive electrode active material has the same type of crystal structure as the solid electrolyte.
[0031] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer. The positive electrode current collector has a rectangular shape in a plan view, such as a sheet, foil or plate. There is no particular limitation on the material constituting the positive electrode current collector, and known materials used in all-solid-state batteries can be used, including but not limited to stainless steel, aluminum, copper, nickel, iron, titanium, carbon or their alloys. The positive electrode active material layer is capable of reversibly absorbing and releasing lithium ions. The positive electrode active material layer includes a positive electrode active material and may further include a solid electrolyte. In addition, if necessary, a conductive aid, a binder, a filler, a dispersant, etc. may also be included, which are known materials contained in the active material layer of the positive electrode sheet of the all-solid-state battery.
[0032] When the negative electrode sheet includes a negative electrode active material, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer, wherein the negative electrode current collector has a rectangular shape in a plan view, such as a sheet, foil or plate. The material of the negative electrode current collector is not particularly limited, and known materials that can be used for all-solid-state batteries can be appropriately used. Examples of materials for the negative electrode current collector include stainless steel, aluminum, copper, nickel, iron, titanium, carbon, and the like. The negative electrode sheet active material layer may include one or more negative electrode active materials that form an alloy or compound with lithium, and the negative electrode active material layer may also include known materials such as a binder contained in the positive electrode sheet active material layer of the all-solid-state battery.
[0033] The solid electrolyte layer is disposed between the positive electrode sheet and the negative electrode sheet, specifically between the positive electrode sheet active material layer and the negative electrode sheet active material layer. The solid electrolyte layer has a rectangular shape in a plan view, such as a sheet, foil or plate, and includes a crystalline solid electrolyte capable of moving ions.
[0034] The type of crystal structure refers to the classification according to the specific arrangement of actual particles (atoms, ions or molecules) in the crystal, and the crystal structure can be determined by X-ray diffraction and electron beam diffraction. In this application, the crystal structure type is classified based on the crystalline solid electrolyte. In this application, the solid electrolyte includes at least one of a perovskite solid electrolyte, an antiperovskite solid electrolyte and a LISICON solid electrolyte. The above arrangement can make the battery electrochemical performance better. It should be noted that the elements and / or proportions constituting the solid electrolyte, the positive active material and the negative active material are not required to be the same in this application, only the type of crystal structure needs to be the same.
[0035] The positive electrode active materials and / or negative electrode active materials are collectively referred to as electrode materials. In the present application, when the solid electrolyte includes at least one of a perovskite solid electrolyte, an antiperovskite solid electrolyte and a LISICON solid electrolyte, using a material with the same crystal structure type as the solid electrolyte as the electrode material can not only increase the lattice matching at the interface, reduce the interface impedance, and allow lithium ions to pass through the interface quickly, but also improve the electrochemical performance of the battery.
[0036] Among them, the all-solid-state battery can be a primary battery or a secondary battery, and the lithium ions are charged and discharged while moving between the positive electrode and the negative electrode.
[0037] In some optional embodiments, the positive electrode active material, the negative electrode active material and the solid electrolyte have the same crystal structure.
[0038] That is, by selecting a positive electrode active material having the same crystal structure as the solid electrolyte and a negative electrode active material to assemble together to form an all-solid-state battery, the interface resistance can be effectively reduced through the above arrangement.
[0039] Since the present application requires that the electrode material and the solid electrolyte have the same crystal structure type, and not all materials can be used as solid electrolytes, the corresponding electrode material is selected based on the crystal structure type of the crystalline solid electrolyte.
[0040] In some optional embodiments, the solid electrolyte is an antiperovskite solid electrolyte.
[0041] The positive electrode active material is an antiperovskite positive electrode active material; and / or, the negative electrode active material is an antiperovskite negative electrode active material.
[0042] It should be noted that the antiperovskite type includes single antiperovskite, double antiperovskite and layered perovskite structures, which are not limited here. As long as the solid electrolyte is an antiperovskite solid electrolyte, the positive electrode active material is an antiperovskite positive electrode active material; and / or the negative electrode active material is an antiperovskite negative electrode active material, both can increase the lattice matching at the interface.
[0043] Among them, antiperovskite-type positive electrode active materials have high capacity and relatively high electronic conductivity.
[0044] Antiperovskite solid electrolytes not only have good interface stability with metallic lithium, but also have a small Young's modulus and a low melting point, which is conducive to processing and effectively improves solid-solid interface contact.
[0045] Optionally, the solid electrolyte comprises at least one of Li7O2X3, Li3OX and Li2OHX, wherein X comprises F - , Cl - Br - ,I - 、NO 2- NH 2- , BH 4- and BF 4- At least one of the above solid electrolytes. All of the above solid electrolytes are anti-perovskite solid electrolytes.
[0046] Optionally, the positive electrode active material includes Li x TM y ChD b , and / or, the negative electrode active material includes amorphous Li x TM y ChD b , where TM is a transition metal, Ch is a chalcogen element, and D is O or B a C 1-a, B is selected from at least one of negative monovalent anions and negative monovalent anion clusters, C is selected from at least one of negative trivalent anions and negative trivalent anion clusters, 0.5≤x≤8, 0.8≤y≤1.1, 0.25≤a≤0.75, 0.8≤b≤1.2.
[0047] It can be understood that the above-mentioned positive electrode active material and negative electrode active material are both antiperovskite materials, wherein the positive electrode active material is an antiperovskite crystalline phase, and the negative electrode active material is an amorphous antiperovskite material.
[0048] It should be noted that the element composition and ratio of the positive electrode active material and the negative electrode active material may be the same, or at least one of the element composition and ratio may be different. Those skilled in the art may make a selection according to actual needs.
[0049] Optionally, TM includes at least one of Fe, Co, Mn, Ni, Cu, Cr, V, Ti, W, Si, Sn and Nb; Ch includes at least one of S, Se and Te; B includes F - , Cl - Br - ,I - , H - OH - 、BH4 - NH2 - 、NO2 - and CN - At least one of; C includes N 3- 、(PO4) 3- 、(SbO4) 3- and (AsO4) 3- At least one of .
[0050] Among them, the antiperovskite positive electrode active materials include but are not limited to Li2FeTe(N 0.5 Cl 0.5 )、Li2FeTe(N 0.5 F 0.5 )、Li2FeSe(N 0.5 Cl 0.5 ), Li2FeTeO or Li2FeSO, etc. The antiperovskite negative electrode active material includes but is not limited to amorphous LiFeSO, amorphous Li3FeSO and amorphous Li5FeSO.
[0051] In some optional embodiments, the solid electrolyte is a LISICON solid electrolyte; the positive electrode active material is a positive electrode active material having a LISICON crystal structure; and / or the negative electrode active material is a negative electrode active material having a LISICON crystal structure.
[0052] Optionally, the solid electrolyte includes Li 14 ZnGe4O 16 , Li 3+x Cr 1-x Ge x O4, Li 3.6 Ge 0.6 V 0.4 O4, Li 4- 2x Co x GeO4, Li 3.25 Si 0.25 P 0.75 O4, Li 3.53 (Ge 0.75 P 0.25 ) 0.7 V 0.3 O4, Li4Al 1 / 3 Si 1 / 6 Ge 1 / 6 P 1 / 3 O4, and Li 3.5 Ge 0.5 V 0.5 At least one of O4, wherein 0≤x≤0.5. The crystal structure type of the solid electrolyte is LISICON type, and optionally, the material has multiple types.
[0053] Optionally, the positive electrode active material includes Li3V2(PO4)3; and / or, the negative electrode active material includes LiV2(PO4)3.
[0054] The crystal structure type of the above LiV2(PO4)3 is LISICON type. Since LiV2(PO4)3 can realize reversible lithium insertion and extraction, it can be used as a positive electrode active material or a negative electrode active material.
[0055] An embodiment of the present application provides an electrical device, which includes the all-solid-state battery provided in the above embodiment, and the all-solid-state battery is used to provide electrical energy to the electrical device.
[0056] That is, the electric device uses the above-mentioned all-solid-state battery as a power source, and the electric device may be, but is not limited to, a mobile phone, a tablet, a laptop, an electric toy, an electric tool, a battery car, an electric car, a ship, a spacecraft, etc. Among them, the electric toy may include a fixed or mobile electric toy, for example, a game console, an electric car toy, an electric ship toy, an electric airplane toy, etc., and the spacecraft may include an airplane, a rocket, a space shuttle, a spacecraft, etc.
[0057] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0058] Example 1
[0059] An all-solid-state battery is prepared by the following method:
[0060] In a solid-state battery mold with a diameter of 10 mm, first add 50 mg of anti-perovskite solid electrolyte material Li2OHCl powder, and press it into a sheet at a pressure of 300 MPa to serve as the solid electrolyte layer.
[0061] The antiperovskite positive electrode active material Li2FeSO powder, the antiperovskite solid electrolyte material Li2OHCl powder and the conductive agent (Super P) were mixed evenly in a mass ratio of 70:15:15 to prepare a composite positive electrode powder. The composite positive electrode powder was spread on any side of the solid electrolyte layer and hot-pressed at 300 MPa and 70°C to ensure that the obtained positive electrode active material layer was in close contact with the solid electrolyte layer.
[0062] A metal lithium sheet is attached to the other side of the solid electrolyte layer away from the positive electrode active material layer as the negative electrode and assembled into an anti-perovskite positive electrode / anti-perovskite electrolyte / metal lithium all-solid-state battery.
[0063] Figure 1 The charge and discharge curves of the anti-perovskite cathode / anti-perovskite electrolyte / metal lithium all-solid-state battery and the AC impedance spectra of some components provided in Example 1; wherein Figure 1 a is the charge and discharge curve of the antiperovskite cathode / antiperovskite electrolyte / metal lithium all-solid-state battery. Figure 1 b is the AC impedance spectrum of Li2OHCl and Li2FeSO / Li2OHCl.
[0064] according to Figure 1 a, its first cycle discharge capacity is as high as over 230mAh / g.
[0065] The steps of Example 1 were repeated to prepare a single antiperovskite electrolyte layer ( Figure 1 b) and the composite layer of antiperovskite cathode / antiperovskite electrolyte ( Figure 1b), the AC impedance spectra of the above samples were measured by two-electrode method using an electrochemical workstation. The test environment was room temperature, a perturbation voltage of 20 mV was applied, and the frequency range was 7 MHz to 1 Hz. The resistance R1 of Li2OHCl and the resistance R2 of Li2FeSO / Li2OHCl were obtained as follows: Figure 1 As shown in b.
[0066] according to Figure 1 As can be seen from b, due to the high total conductivity of Li2FeSO in Li2FeSO / Li2OHCl, its impedance contribution to R2 can be ignored. Therefore, the interface impedance between the solid electrolyte layer and the negative electrode sheet can be obtained by R2-R1, and then multiplied by the interface area between the two to obtain the surface resistance. The calculated surface resistance is 18.4Ω / cm 2 .
[0067] Example 2
[0068] The antiperovskite positive electrode / antiperovskite electrolyte / antiperovskite negative electrode all-solid-state battery is different from Example 1 only in that:
[0069] Li2O, Fe2O3 and Fe2S3 were used as raw materials, weighed in a stoichiometric ratio of 3:1:2, and ball milled at a ball milling speed of 500 rpm for 8 h in a high-energy planetary ball mill to obtain an amorphous lithium-poor negative electrode LiFeSO.
[0070] The amorphous lithium-poor negative electrode LiFeSO, nitrile rubber, conductive carbon black and lithium salt LiTFSI were mixed and homogenized in a mass ratio of 85:5:15:1, and the negative electrode sheet was obtained after coating and roller pressing.
[0071] Among them, the structural schematic diagram of the antiperovskite positive electrode / antiperovskite electrolyte / antiperovskite negative electrode all-solid-state battery is as follows Figure 2 shown.
[0072] Example 3
[0073] The difference between it and Example 2 is only that:
[0074] Spinel structure LiNi 1.5 Mn 0.5 O4 replaces the anti-perovskite positive electrode active material Li2FeSO powder in Example 2.
[0075] Example 4
[0076] The difference between it and Example 1 is only that:
[0077] In a solid-state battery mold with a diameter of 10 mm, 30 mg of LiSICON-type Li 14 ZnGe4O16 The powder is pressed into sheets under a pressure of 300MPa to serve as a solid electrolyte layer.
[0078] The positive electrode Li3V2(PO4)3 powder of LISICON structure, Li 14 ZnGe4O 16 and a conductive agent (Super P) are uniformly mixed in a mass ratio of 70:15:15 to make a composite positive electrode powder. The composite positive electrode powder is spread on any side of the solid electrolyte layer and hot-pressed at 300 MPa and 70° C. to ensure that the obtained positive electrode active material layer is in close contact with the solid electrolyte layer.
[0079] A metal lithium sheet is attached to the other side of the solid electrolyte layer away from the composite positive electrode layer as the negative electrode and assembled into a LISICON type positive electrode / LISICON type electrolyte / metal lithium all-solid-state battery.
[0080] Comparative Example 1
[0081] A spinel structure positive electrode / anti-perovskite electrolyte / LiIn alloy solid-state battery is prepared by the following preparation method:
[0082] In a solid-state battery mold with a diameter of 10 mm, 30 mg of anti-perovskite solid electrolyte material Li2OHCl powder was first added and pressed into a sheet at a pressure of 300 MPa to serve as the solid electrolyte layer.
[0083] The spinel structure LiNi 1.5 Mn 0.5 O4 powder, antiperovskite solid electrolyte material Li2OHCl powder and conductive agent (Super P) are evenly mixed in a mass ratio of 70:15:15 to prepare composite positive electrode powder. The composite positive electrode powder is spread on any surface of the solid electrolyte layer and hot-pressed at 300 MPa and 70°C to ensure close contact between the obtained positive electrode active material layer and the solid electrolyte layer.
[0084] A LiIn alloy electrode is attached to the other side of the solid electrolyte layer away from the positive electrode active material layer to assemble a spinel structure positive electrode / anti-perovskite electrolyte / LiIn alloy solid-state battery.
[0085] Figure 3 middle, Figure 3 a is a charge and discharge curve diagram of the anti-perovskite positive electrode / anti-perovskite electrolyte / metal lithium all-solid-state battery provided in Comparative Example 1, Figure 3 b is the impedance spectrum before and after charging and discharging.
[0086] according to Figure 3a. The first-cycle discharge capacity of the spinel structure positive electrode / anti-perovskite electrolyte / LiIn alloy solid-state battery is only 58mAh / g.
[0087] Before and after the first cycle of battery charge and discharge, an electrochemical workstation was used to test the AC impedance spectrum using the two-electrode method. The test environment was room temperature, a perturbation voltage of 20 mV was applied, and the frequency range was 7 MHz to 1 Hz. Figure 3 b It can be seen that the resistance of the battery before the first cycle of charge and discharge is 75Ω, and the resistance of the battery after the first cycle of charge and discharge is 13526Ω.
[0088] Comparative Example 2
[0089] A half-cell of Si negative electrode / solid electrolyte Li2OHCl / lithium metal is prepared by the following preparation method:
[0090] In a solid-state battery mold with a diameter of 10 mm, 30 mg of antiperovskite solid electrolyte material Li2OHCl powder is first pressed into sheets at a pressure of 300 MPa to serve as the solid electrolyte layer.
[0091] Silicon powder, nitrile rubber, conductive carbon black and lithium salt LiTFSI were mixed and homogenized in a mass ratio of 85:5:15:1, and the coating roller was pressed on copper foil to obtain a negative electrode sheet as a Si negative electrode. The Si negative electrode was laid flat on one side of the solid electrolyte and hot-pressed at 300MPa and 70°C to make the silicon negative electrode in close contact with the solid electrolyte layer; a lithium metal electrode was attached to the other side of the solid electrolyte layer to assemble a Si negative electrode / Li2OHCl / lithium metal half-cell.
[0092] Figure 4 middle, Figure 4 a is the charge and discharge curve of the half-cell of Si negative electrode / Li2OHCl / lithium metal, Figure 4 b is the impedance spectrum before and after charging and discharging.
[0093] according to Figure 4 a. Due to some side reactions during the charge and discharge process of the Si negative electrode / Li2OHCl / lithium metal half-cell, the first cycle discharge capacity is 4800mAh / g, which is higher than the theoretical specific capacity of the Si negative electrode of 3500mAh / g.
[0094] Before and after the first cycle of battery charge and discharge, an electrochemical workstation was used to test the AC impedance spectrum using the two-electrode method. The test environment was room temperature, a perturbation voltage of 20 mV was applied, and the frequency range was 7 MHz to 1 Hz. Figure 4 From b, we can see that the resistance of the battery before the first cycle of charge and discharge is 920Ω, and the resistance after the first cycle of charge and discharge is 1536Ω.
[0095] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. An all-solid-state battery, characterized in that: The invention comprises a positive electrode sheet and a negative electrode sheet, and a solid electrolyte layer disposed between the positive electrode sheet and the negative electrode sheet, wherein the solid electrolyte layer comprises a crystalline solid electrolyte, and the solid electrolyte comprises at least one of a perovskite solid electrolyte, an anti-perovskite solid electrolyte and a LISICON solid electrolyte, and the positive electrode sheet comprises a positive electrode active material; Wherein, the negative electrode sheet includes a negative electrode active material, and at least one of the positive electrode active material and the negative electrode active material has the same type of crystal structure as the solid electrolyte; or, the negative electrode sheet is metallic lithium, and the positive electrode active material has the same type of crystal structure as the solid electrolyte.
2. The all-solid-state battery according to claim 1, characterized in that: The positive electrode active material, the negative electrode active material, and the solid electrolyte have the same type of crystal structure.
3. The all-solid-state battery according to claim 1, characterized in that: The solid electrolyte is an antiperovskite solid electrolyte; The positive electrode active material is an antiperovskite positive electrode active material; and / or, the negative electrode active material is an antiperovskite negative electrode active material.
4. The all-solid-state battery according to claim 3, characterized in that: The solid electrolyte comprises at least one of Li7O2X3, Li3OX and Li2OHX, wherein X comprises F - , Cl - Br - ,I - 、NO 2- NH 2- , BH 4- and BF 4- At least one of .
5. The all-solid-state battery according to claim 4, characterized in that: The positive electrode active material includes Li x TM y ChD b , and / or, the negative electrode active material includes amorphous Li x TM y ChD b ; Where TM is a transition metal, Ch is a chalcogen element, and D is O or B a C 1-a , B is selected from at least one of negative monovalent anions and negative monovalent anion clusters, C is selected from at least one of negative trivalent anions and negative trivalent anion clusters, 0.5≤x≤8, 0.8≤y≤1.1, 0.25≤a≤0.75, 0.8≤b≤1.
2.
6. The all-solid-state battery according to claim 5, characterized in that: TM includes at least one of Fe, Co, Mn, Ni, Cu, Cr, V, Ti, W, Si, Sn and Nb; Ch includes at least one of S, Se and Te; B includes F - , Cl - Br - ,I - , H - OH - 、BH4 - NH2 - 、NO2 - and CN - At least one of; C includes N 3- 、(PO4) 3- 、(SbO4) 3- and (AsO4) 3- At least one of .
7. The all-solid-state battery according to claim 1, characterized in that: The solid electrolyte is a LISICON type solid electrolyte; The positive electrode active material is a positive electrode active material having a LISICON crystal structure; and / or the negative electrode active material is a negative electrode active material having a LISICON crystal structure.
8. The all-solid-state battery according to claim 6, characterized in that: The solid electrolyte includes Li 14 ZnGe4O 16 , Li 3+x Cr 1-x Ge x O4, Li 3.6 Ge 0.6 V 0.4 O4, Li 4-2x Co x GeO4, Li 3.25 Si 0.25 P 0.75 O4, Li 3.53 (Ge 0.75 P 0.25 ) 0.7 V 0.3 O4, Li4Al 1 / 3 Si 1 / 6 Ge 1 / 6 P 1 / 3 O4, and Li 3.5 Ge 0.5 V 0.5 At least one of O4, where 0≤x≤0.
5.
9. The all-solid-state battery according to claim 6, characterized in that: The positive electrode active material includes Li3V2(PO4)3; and / or, the negative electrode active material includes LiV2(PO4)3.
10. An electrical device, characterized in that: The all-solid-state battery comprises the all-solid-state battery as described in any one of claims 1 to 9, wherein the all-solid-state battery is used to provide electrical energy to the electrical device.
Citation Information
Patent Citations
All-solid-state lithium battery
CN106876707A
All-solid battery
CN111213276A
Electrolyte layer-anode composite member, and cell structure
CN111801827A
Power battery special for new energy automobile
CN209249604U
Transition-metals doped lithium-rich Anti-perovskites for cathode applications
US20180006306A1